1978
DOI: 10.2136/sssaj1978.03615995004200010028x
|View full text |Cite
|
Sign up to set email alerts
|

Leguminous Plants Increase Sycamore Growth in Northern Alabama

Abstract: Tree growth in a 2‐year‐old sycamore (Platanus occidentalis L.) plantation in northern Alabama significantly increased over the following 4 years after three clovers and two vetches were grown with the trees. Leguminous plants were chosen to: (i) provide weed control through good ground coverage, (ii) maintain a low profile, (iii) grow during the cool season so as not to compete with the sycamore, (iv) provide cover for several years after establishment through their ability to reseed, and (v) make additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1981
1981
1997
1997

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…In northern Alabama, tree growth in a two-year-old sycamore (Platanus occidentalis) plantation significantly increased during four years in which clover and vetch were grown within the plantation [23].…”
Section: Multicropping Hardwoods With Agricultural Cropsmentioning
confidence: 99%
“…In northern Alabama, tree growth in a two-year-old sycamore (Platanus occidentalis) plantation significantly increased during four years in which clover and vetch were grown within the plantation [23].…”
Section: Multicropping Hardwoods With Agricultural Cropsmentioning
confidence: 99%
“…villosa, and that higher seeding rates reduced yield. Nordstrom (1982) (Rietveld 1983 Haines et al (1978) found that V. villosa was one of five legumes used as ground cover which increased tree growth in a Platanus occidentalis L. plantation in northern Alabama (U.S.A.). A race of V. sativahas been found to mimic Lens esculenra in seed size and shape and has spread and dominated crops of the latter (Rowlands 1959).…”
Section: Geographical Distributionmentioning
confidence: 99%
“…Haines, Haines and White (1978) reported encouraging results in 'a young sycamore (Pseudoplatanus occidentalis) plantation in northern Alabama. After four years with a clover cover crop, Trifolium spp, the volume of a six-year old plantation was7TTAT.…”
Section: Nitrogen-fixing Organismsmentioning
confidence: 99%